Design and construction of a low-cost, low-input Open Top Chamber field warming setup to assess aboveground plant response to global warming - Hauser, Joshua; Kooijman, Pieter C.; Paddon, Edward N.D.; Verhoeven, Ava; Kalisvaart, Jasmijn; Meesters, Adam N.; Snoek, Basten L.; van Zanten, Martijn (Frontiers in Plant Science, 2025)
Climate change drastically impacts the development, physiology, and phenology of plants. Conducting experiments to elucidate plant responses to high temperatures is essential to understanding and mitigating the impact of global warming. Typically, empirical research assessing the impact of (high) temperatures is conducted in climate-controlled growth chambers, cabinets, or greenhouses. Although informative, such experiments ignore the effects that seasonal, daily, and minute-scale changes in environmental parameters can have on temperature responsiveness. Semi-controlled field warming setups are therefore required in which average temperatures are consistently raised whereas other environmental parameters, such as diurnal fluctuations in temperature, rainfall, changes in light intensity, and photoperiod, remain reasonably unaffected. Here, we present a low-cost, low-input (in terms of construction materials and energy expenditure), field warming setup in which heating cables were combined with a PMMA/acrylic Open Top Chamber (OTC) and show that this setup can effectively raise internal temperatures by ~3 °C-5°C above ambient in field conditions. Assessing shoot phenotypes of cold-tolerant common snowdrops (Galanthus nivalis), Arabidopsis thaliana natural accessions, and tomato (Solanum lycopersicum) confirmed that the OTC setup can be used to study shoot responsiveness to high temperatures in the context of the stochastic outdoor environment. The low-cost materials used, combined with provided construction details and software code, should encourage the swift development of warmed OTCs by researchers worldwide.